A reflection on the trading of pollution rights via land use exchanges and controls: Coase Theorems, Coase's land use parable, and Schumpeterian innovations. (April 2020) - Lai, Lawrence W.C.; Lorne, Frank; Davies, Stephen N.G.
Highlights: First neo-institutional inquiry into use of landuse planning in reducing carbon emission. First attempt to relate Coasean trading of pollution to spatial policies. Reinterpretation of TDR and land readjustment as pollution control mechanisms. Abstract: This monograph attempts to connect various versions of the Coase Theorem to carbon trading as a means to help ameliorate global warming and manifests their relevance to designs of land-based environmental policies with reference to such established land use planning tools as zoning and the transfer of development rights. These land-based policies, which are in line with the received concept of "transfer of development rights", are demonstrably sustainable and they are easier to monitor physically than trading in greenhouse gas emissions. The discussion is in support of and articulates with the "land use, land-use change and forestry" (LULUCF) endeavours of the Kyoto Protocol and is timely, as global warming is a real environmental issue. The supposition that Coasian economics, under the spell of the false plan/market dichotomy in both the academic and the political arena, is inherently alien to sustainable development is wrong. The argument below involves four versions of Coase Theorem. Two were formulated by George Stigler based on Coase's "The Problem of Social Cost" (1960), a treatise against Arthur Pigou's concept of pollution. The remaining two are those that in The Firm, the Market and the Law Coase considered his actual theorems. The theorems are supportive of government planning rules including "transfer of development rights" (TDR) and land readjustment. Despite seeming to be restrictive quotas, they actually enable innovations that can promote sustainable development, as envisaged in Yu's Coasian-Schumpeterian model of creative destruction (Yu et al., 2000). Standard supply and demand graphs and examples are used to demonstrate the compatibility of our reasoning with standard neoclassical economic tools.